DEVELOPMENT OF PISA TYPES OF QUESTIONS AND ACTIVITIES CONTENT SHAPE AND SPACE CONTEXT PANDEMIC PERIOD - Risda Intan Sistyawati; Zulkardi Zulkardi; Ratu Ilma Indra Putri; Samsuriyadi Samsuriyadi; Zahra Alwi; Sisca Puspita Sepriliani; Ayu Luviyanti Tanjung; Riszky Pabela Pratiwi; Shinta Aprilisa; Duano Sapta Nusantara; Meryansumayeka Meryansumayeka; Jayanti Jayanti (Jurnal Infinity, 2023)
This research belongs to the type of development research, which consists of the main stages, including preliminary design and formative evaluation. This study aims to obtain valid and practical PISA-type development questions consisting of initial design, self-evaluation, expert review, one-to-one, and small group. The emergence of this research is due to the low mathematical literacy of students in Indonesia. This study took a particular research subject for grade IX junior high school students in Palembang City. From this study, the results obtained include the development of PISA-type questions and activities using the context of social distancing during the pandemic.